Chinese expert consensus on clinical practice of MET detection in non-small cell lung cancer - Bai, Qianming; Shi, Xiaohua; Zhou, Xiaoyan; Liang, Zhiyong; Lu, Shun; Wu, Yilong (Therapeutic advances in medical oncology, 2024)
Mesenchymal epithelial transition (MET) factor alteration in non-small cell lung cancer (NSCLC) includes MET exon 14 skipping alteration (METex14 skipping), MET gene amplification, MET gene mutation (mainly kinase domain mutation), MET gene fusion, and MET protein overexpression. The incidence of METex14 skipping in patients with NSCLC is 0.9–4.0%. At present, drugs targeting METex14 skipping have been approved in China and other countries like Japan and USA. Patients with advanced NSCLC should undergo testing, including METex14 skipping, to screen the population with benefit from targeted therapy with MET inhibitors. The incidence of de novo MET gene amplification in NSCLC patients is 1–5%, the incidence of acquired MET gene amplification in epidermal growth factor receptor tyrosine kinase inhibitor (TKI)-resistant patients is 5–50%, and the incidence in anaplastic lymphoma kinase (ALK) TKI-resistant patients is about 13%; the incidence of MET protein overexpression in NSCLC patients is 13.7–63.7%. Several clinical trials on MET gene amplification and MET protein overexpression are ongoing, which have demonstrated their important guiding significance as biomarkers in the clinical treatment with MET inhibitors. Accurate detection of MET alterations is a prerequisite for MET inhibitor therapy. Since there are many types of MET alterations and related testing methods, as well as many problems and challenges during clinical testing, further sorting and standardization are required. Combined with clinical practice experience, literature review, and expert discussion, the writing group developed this consensus on the three main types of MET alterations (METex14 skipping, MET gene amplification, and MET protein overexpression) in order to guide the practical applications of clinical MET testing.